Islamic Law and Digital Evidence: Comparative Perspectives from Bangladesh, Malaysia, and the UAE - Shadeka Jannat (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2026)
The developments in digital technology has revolutionized the approach of modern judicial systems to collect, authenticate and present evidence. Nowadays, electronic evidence (comprising digital documents, emails, video files, metadata and forensic digital images) is a core part of litigation. Regrettably, there is a great deal of dispute over whether it is in line with the Koran. This research explores the admissibility of digital evidence in Bangladesh, Malaysia and the UAE under Islamic law. This article examines with a comparative and religious legal method some recent constitutional impacts, namely the UAE Cybercrime Law 2021, Malaysia’s Evidence Act 1990 (S. 90A), and Bangladesh’s Evidence (Amendment) Act 2022, discussing adherence to traditional fiqh principles qarīnah (circumstantial evidence), iqrār (confession), bayyinah (proof), and shahādah (testimony). The results indicate that the digital evidence meets these standards of authenticity, justifiable acquisition, certainty and integrity can be Shariah compliant. The Shariah-Compliant Digital Evidence Framework (SCDEF) that the study will proposes is an integration of forensic science and Islamic law to make justice compatible with maqāṣid al-Sharīʿah if it is based on protective factors such as moral purity, justice and factuality.